2019
DOI: 10.12791/ksbec.2019.28.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Quality, and Early Growth and Fruit Productivity after Transplanting of Squash as Affected by Plug Cell Size and Seedling Raising Period

Abstract: This research was conducted to figure out the optimal size of the plug cell and seedling raising period in 'Nongwoo' and 'Nonghyeop' cultivars. In the first experiment on effect of plug cell size on growth of squash, seedlings were transplanted into hydroponic cultivation beds at different growing stages: Those in 32-cell trays with 3-4 true leaves at 25 days after sowing, those in 50-cell trays with 2 true leaves at 15 days after sowing, those in 105-cell trays just before a true leaf development, and those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…5, 2021 seedlings to show shoot growth. However, Kim et al (2019) reported that smaller cell size leads to quicker root pruning after sowing, thereby moving up the time for planting, which as a result was effective in growth after planting. Hwang et al (2018) reported that silver grass for landscaping did not show good growth with smaller cells when raising seedlings in plug trays, but seedlings raised in small cells showed excellent growth about 3 months after planting.…”
Section: Resultsmentioning
confidence: 99%
“…5, 2021 seedlings to show shoot growth. However, Kim et al (2019) reported that smaller cell size leads to quicker root pruning after sowing, thereby moving up the time for planting, which as a result was effective in growth after planting. Hwang et al (2018) reported that silver grass for landscaping did not show good growth with smaller cells when raising seedlings in plug trays, but seedlings raised in small cells showed excellent growth about 3 months after planting.…”
Section: Resultsmentioning
confidence: 99%
“…Cabbage seedlings grown in plug trays with larger cell sizes had relatively better growth, and the seedlings with better growth led to increased productivity [40]. However, Kim et al [41] reported that zucchini seedlings grown in a 32-cell plug tray showed lower quality of the first harvested fruit than those grown in plug trays with 50, 105, and 163 cells. The optimal cell size in the plug tray should be determined carefully considering the seedling growth characteristics, cultivation area, period, and resources used during the nursery process.…”
Section: Seedling Growth In Chinese Cabbage As Affected By Cell Size ...mentioning
confidence: 99%
“…Selection of plug tray cell size is highly dependent on the crop species, grafting method, and seedling production period (Yu et al, 2002;Yaping and Diankui, 2005;Babaj et al, 2012;Kim et al, 2019). Also, commercial nurseries tend to use plug trays with more cells and smaller cell size to increase the number of plants produced, to decrease the space for seedling production and to reduce propagation costs per plant (Dufault and Waters, 1985;Oh et al, 2014).…”
Section: Cell Size Of Plug Traymentioning
confidence: 99%